All I Really Need to Know I Learned in Kindergarten Uncommon thoughts on common things - Robert L. Fulghum (U.S.A Villard Books, 1986)
Fulghum writes from the heart with wit and real insight about everyday things, about small lives with large meanings. These essays may make readers chuckle or weep or simply pause to reflect on their own lives, but readers will never be left unaffected.